2001
DOI: 10.3171/spi.2001.94.2.0323
|View full text |Cite
|
Sign up to set email alerts
|

Use of folded vascularized rib graft in anterior fusion after treatment of thoracic and upper lumbar lesions

Abstract: ✓ For lesions involving the anterior and/or middle column of the spine, an anterior approach is adequate for curetting the lesion and restoring spinal stability. Materials such as autogenous bone grafts, cages with bone chips, some artificial materials, or allografts are used as strut materials. Rib material is usually removed when the anterior approach is conducted for thoracic or thoracolumbar lesions. A rib itself is not rigid enough to support the load, and a bone union is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 33 publications
(33 reference statements)
0
21
1
2
Order By: Relevance
“…Additionally, the harvesting of bone for grafting in situations such as spinal fusion also leads to rib defects [2]. Currently, rib defects are left unrepaired because they have little impact on respiratory function and there is no clear robust method for rib regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the harvesting of bone for grafting in situations such as spinal fusion also leads to rib defects [2]. Currently, rib defects are left unrepaired because they have little impact on respiratory function and there is no clear robust method for rib regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of blood supply or inflammatory cell infiltration into the artificial PEG hydrogel may have contributed to its poor performance in this respect. 11,13 In addition, antibiotics administered to treat a patient may be rendered ineffective because of this reduced blood supply. Therefore, although a previous study found that PEG hydrogel sealant did not directly damage the brain parenchyma, 14 the present study indicated that it may cause cortical damage indirectly via granuloma formation on the brain surface.…”
Section: Granulation/abscess Formation In the Cerebral Cortex And Cormentioning
confidence: 99%
“…27,30,31 McBride and Bradford 27 used an additional structural cortical allograft spacer in their early series. In 1999, Deen et al 30 reported their experience placing a titanium mesh cage and pedicled rib flap adjacent to one another to fill corpectomy defects in 3 patients: 2 with osteomyelitis and 1 with plasmacytoma.…”
Section: Discussionmentioning
confidence: 99%